Proceedings of the Ocean Drilling Program 1988
DOI: 10.2973/odp.proc.sr.103.143.1988
|View full text |Cite
|
Sign up to set email alerts
|

Cenozoic Calcareous Nannofossils from the Galicia Margin, Ocean Drilling Program Leg 103

Abstract: Ocean Drilling Program Leg 103 occupied five sites on the Galicia margin, northwest of the Iberian Peninsula. Two holes (Holes 637A and 638B) yielded significant Cenozoic sedimentary sections ranging from late Miocene to late Pleis tocene in age. From the nannofossil stratigraphy, one hiatus is recognized in Hole 637A (2.35-2.4 Ma), whereas two hia tuses (one at 1.9-2.6 Ma and another at 3.5-3.7 Ma) are recognized in Hole 638B. Sediment-accumulation rates for the Cenozoic portions of these two holes have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1988
1988
2001
2001

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…2). Wei et al (1988) also found that the D. brouweri-C. pelagicus ratio decreased sharply after about 2.5 Ma on the Galicia Margin. Another predominantly coolwater interval also occurs in Zone NN13 in Leg 161 holes.…”
Section: Synthesismentioning
confidence: 76%
See 2 more Smart Citations
“…2). Wei et al (1988) also found that the D. brouweri-C. pelagicus ratio decreased sharply after about 2.5 Ma on the Galicia Margin. Another predominantly coolwater interval also occurs in Zone NN13 in Leg 161 holes.…”
Section: Synthesismentioning
confidence: 76%
“…In the Neogene, however, several discoasters (D. variabilis, D. intercalaris, D. tamalis, and D. asymmetricus) are believed to have preferred cool waters (Bukry, 1981;Rio et al, 1990a). A single discoaster species, Discoaster brouweri, which has a well-established preference for warm waters (e.g., Bukry, 1978, Siesser, 1975Muller, 1985, Wei et al, 1988, was thus selected as the warmwater proxy for this study.…”
Section: Paleoclimatologymentioning
confidence: 99%
See 1 more Smart Citation
“…In the Neogene, however, several discoasters (D. variabilis, D. intercalaris, D. tamalis, and D. asymmetricus) are believed to have preferred cool waters (Bukry, 1981;Rio et al, 1990b). A single discoaster species, Discoaster brouweri, which has a well-established preference for warm waters (e.g., Bukry, 1978Bukry, , 1981Siesser, 1975;Müller, 1985;Wei et al, 1988) was thus selected as the warm-water proxy for this study.…”
Section: Nannofossil Climatic Proxiesmentioning
confidence: 99%
“…Using two species that vary inversely in relative abundance rather than using the absolute abundance of only one species avoids potential error caused by variations in the density of specimens sedimented on a slide. Siesser and de Kaenel (1999) used a similar method of investigation for the Pliocene in the western Mediterranean, and Wei et al (1988) used a ratio of these two species on the Galicia Margin. Samples investigated are plotted against the timescale (Fig.…”
Section: Nannofossil Climatic Proxiesmentioning
confidence: 99%